Brown gold for black gold - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The emergence of Equatorial Guinea, finally, as a major oil producer it expects to become the fourth largest exporter within five years is also producing a revival in the country s cocoa plantations. Having won several international prizes in...